2008
DOI: 10.1002/art.24105
|View full text |Cite
|
Sign up to set email alerts
|

Effects of activity strategy training on pain and physical activity in older adults with knee or hip osteoarthritis: A pilot study

Abstract: Objective. To examine effects of activity strategy training (AST), a structured rehabilitation program taught by occupational therapists and designed to teach adaptive strategies for symptom control and engagement in physical activity (PA). Methods. A randomized controlled pilot trial was conducted at 4 sites (3 senior housing facilities and 1 senior center) in southeastern, lower Michigan. Fifty-four older adults with hip or knee osteoarthritis (mean ؎ SD age 75.3 ؎ 7.1 years) participated. At each site, olde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(33 citation statements)
references
References 44 publications
1
30
0
2
Order By: Relevance
“…[5][6][7][8]17,18,29,34,35 Intervention 2 was some form of arthritis self-management education that also included exercise (15 studies; subjects, n = 1757; women, n = 1406 [80%]). 16,20,[25][26][27][28][30][31][32]40,47,51,[59][60][61] These interventions included both cohort studies using the ASES pain (10 studies; subjects, n = 1035) 5 37.5% (9 of 24) did not describe a control or placebo group, 41.7% (10 of 24) did not adequately describe study exclusion criteria, and 25% (6 of 24) did not adequately describe subject dropout management. Studies with arthritis self-management education with exercise (intervention 2) displayed significantly higher methodological quality scale scores (76.8  13.1 versus 61.6  19.6, P = .03) compared to studies with arthritis self-management education alone (intervention 1).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…[5][6][7][8]17,18,29,34,35 Intervention 2 was some form of arthritis self-management education that also included exercise (15 studies; subjects, n = 1757; women, n = 1406 [80%]). 16,20,[25][26][27][28][30][31][32]40,47,51,[59][60][61] These interventions included both cohort studies using the ASES pain (10 studies; subjects, n = 1035) 5 37.5% (9 of 24) did not describe a control or placebo group, 41.7% (10 of 24) did not adequately describe study exclusion criteria, and 25% (6 of 24) did not adequately describe subject dropout management. Studies with arthritis self-management education with exercise (intervention 2) displayed significantly higher methodological quality scale scores (76.8  13.1 versus 61.6  19.6, P = .03) compared to studies with arthritis self-management education alone (intervention 1).…”
Section: Methodsmentioning
confidence: 99%
“…These studies reported a mean effect size of 0.438  0.07. Forest plots were created for randomized controlled studies that used the ASES pain (13 studies, n = 1925), 6,18,20,[26][27][28][29]34,40,51,[59][60][61] other symptoms (13 studies, n = 1976), 6,18,20,[25][26][27][28][29]34,51,[59][60][61] and function (5 studies, n = 428) 18,20,28,29,34 subscales. Small to moderate standardized mean difference effect sizes were noted for both intervention 1 and intervention 2 for ASES pain (0.37  0.47 versus 0.20  0.32, P = .60) (FIGURE 2), other symptoms (0.25  0.17 versus 0.29  0.29, P = .94) (FIGURE 3), and function (0.17  0.11 versus 0.18  0.21, P = .99) (FIG-URE 4) subscales.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In der EULAR-("European League Against Rheumatism"-) und ebenso in der NICE-("National Institute for Health and Clinical Excellence"-) Leitlinie für die Behandlung der Arthrose wird dieser Ansatz und die Kombination von Patientenedukation und Übungsbe-handlung explizit empfohlen [8,9]. Murphy et al [15] wiesen in einer randomisierten kontrollierten Studie gesteigerte physische Aktivität durch ein ergotherapeutisches Therapieprogramm bei Patienten mit Hüft-und Kniegelenkarthrose nach. Eine weitere Studie weist auf die Reduktion der Operationsnachfrage durch eine Schienenbehandlung der Hand hin [16].…”
Section: Ergotherapie -Grundlagen Und Effektivitätunclassified